2020
DOI: 10.1155/2020/1216303
|View full text |Cite
|
Sign up to set email alerts
|

Association between a TCF4 Polymorphism and Susceptibility to Schizophrenia

Abstract: The basic helix-loop-helix (bHLH) transcription factor 4 (TCF4) had been identified as a susceptibility gene associated with schizophrenia (SCZ) by GWAS, but inconsistent results have been found in other studies. To validate these findings and to reveal the effects of different inheritance models, rs2958182, rs1261085, rs8766, and rs12966547 of the TCF4 gene were genotyped in the Northwest Han Chinese population (448 cases and 628 controls) via a multiplex polymerase chain reaction SNPscan assay. Single SNP, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…the results of their study with previously published reports, they found a noteworthy association between TCF4 rs1261084C/T and SCZ susceptibility [78]. Results of an investigation by Hui et al indicated that another SNP in the TCF4 gene, rs2958182A/T, affected SCZ risk and was associated with lower cognitive performance in the language in these patients [79].…”
Section: Disease Markerssupporting
confidence: 59%
See 1 more Smart Citation
“…the results of their study with previously published reports, they found a noteworthy association between TCF4 rs1261084C/T and SCZ susceptibility [78]. Results of an investigation by Hui et al indicated that another SNP in the TCF4 gene, rs2958182A/T, affected SCZ risk and was associated with lower cognitive performance in the language in these patients [79].…”
Section: Disease Markerssupporting
confidence: 59%
“…Using multiplex polymerase chain reaction- (PCR-) SNPscan assay, Gao et al genotyped 448 SCZ cases and 628 controls from a northwest Han Chinese population and found no significant link between TCF4 rs1261084C/T and the disease. However, by combining the results of their study with previously published reports, they found a noteworthy association between TCF4 rs1261084C/T and SCZ susceptibility [ 78 ]. Results of an investigation by Hui et al indicated that another SNP in the TCF4 gene, rs2958182A/T, affected SCZ risk and was associated with lower cognitive performance in the language in these patients [ 79 ].…”
Section: Discussionmentioning
confidence: 58%
“…TCF4 is known to be intimately related to PTHS (Amiel et al, 2007), and interestingly, in schizophrenia, many altered biological pathways have a significant association with this TF. Since the late 2000s, when the first study associating alterations in TCF4 and schizophrenia was released (Stefansson et al, 2009), several other studies consolidated and demonstrated the relevance of TCF4 in psychotic episodes and bipolar disorder (Gao et al, 2020; Hall et al, 2014; Ripke et al, 2014; Steinberg et al, 2011).…”
Section: Ndd‐associated Multifactorial Disordersmentioning
confidence: 99%
“…no significant differences were observed at the genome level ( P < 10 −8 )] (Moons et al , 2016). Moreover, two studies showed that rs12966547 is not significantly associated with the risk of schizophrenia in the Han Chinese population (Gao et al , 2020; Yin et al , 2019). The genotypic distribution of rs12966547 shows some notable racial differences (based on the HapMap data); for example, the minor allele is A in Caucasians but G in the Chinese.…”
Section: Introductionmentioning
confidence: 99%